Investigation of systems to prevent diversion of opiate drugs in general practice in the UK. Issue 1 (2nd February 2004) - Baker, R; Moss, P; Upton, D; Pankhania, J
Abstract : Background: Statutory regulations govern the procedures that must be followed by general practitioners (GPs) in the UK to minimise the risk of diversion of prescribed opiate drugs for illicit use. However, evidence presented at the trial of Harold Shipman, a GP convicted of murdering patients with diamorphine, suggests that the regulations and monitoring of GPs' prescribing are failing. Aim: To assess the policies followed by general practices in Leicestershire and Rutland with regard to the controlled drugs regulations. Methods: A semi-structured interview was administered to a purposeful sample of lead GPs to explore how their practices applied the regulations. The controlled drugs registers and drug storage facilities in these practices were inspected. A questionnaire was sent to all the remaining practices to seek information about their application of the regulations, any concerns they had about the regulations, and any suggestions for improving them. Results: Of the 142 general practices in Leicestershire, the lead GP in 14 took part in the interviews. Respondents expressed dissatisfaction with current policies including the design of controlled drug registers, and generally supported the reintroduction of an inspection scheme. Ninety (70.9%) of the 127 practices to whom the questionnaire was sent responded and, of these, 31 (34.4%) no longer held a supply of controlled drugs. Those that did hold controlled drugs indicated concern about the regulations, confusion about some aspects including the return and disposal of unused drugs, and a desire for advice and support in the implementation of the regulations. Forty two of the 59 respondents who held a supply of controlled drugs (71.2%) would welcome regular inspection. Conclusion: GPs are confused about the controlled drugs regulations and have little support in implementing them. The suspension of inspection schemes has reduced the amount of advice and support available to them and, in consequence, the regulations are interpreted differently in different practices. These findings are cause for concern about the risk of diversion of controlled drugs, and illustrate how patient safety systems can decay when they are not maintained.